The Influence of Job Environment and Organizational Justice on Employee Performance mediated by Employee Engagement in Hospital Employees - Ella Mayasari; Pardiman Pardiman; Budiar Budiar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of job environment and organizational justice on employee performance mediated by employee engagement at a private hospital in Malang. The sample used was 975 employees from two private hospitals. The sampling technique used a saturated sample by making the entire population the research sample. The respondents' criteria are non-outsourced medical personnel and non-outsourced medical personnel. Questionnaires were used to collect research data which were then processed using AMOS. The results showed that the job environment had a significant effect on employee engagement and also on employee performance. Meanwhile, organizational justice has no significant effect on employee engagement and employee performance. Employee engagement did not succeed in mediating the effect of job environment and organizational justice on employee performance.